PENGEMBANGAN INSTRUMEN PENGUKURAN KUALITAS UDARA MENGGUNAKAN SENSOR PMS7003 - Tanti Tritama Okaem (Megasains, 2022)
Air pollution is one of the global environmental problems. One of the air quality parameters of concern is Particulate Matter 2.5 ug/m (PM2.5) because it causes respiratory health problems. The PM2.5 air quality information is very limited due to the number and operational constraints of the instrument, so the development of air quality measurement equipment using the PMS7003 sensor is carried out. The test was carried out at SPAG Bukit Kototabang for 1 month, the instrument was compared with the MetOne BAM 1020 reference equipment for concentrations of PM2.5 and PM10. This research was conducted using the Plomp development model. The results obtained by the PMS7003 sensor are suitable for measuring the concentration of PM2.5 compared to PM10. The results of PM2.5 testing with reference instruments were obtained, namely correlation 0.68, RMSE 3.83, bias -0.43, MAE 2.91, accuracy 0.92 and PM2.5 concentration on the PMS7003 sensor increased when humidity was above 90%.